Teachers' Efforts in Integrating Deep Learning-Based Instruction in the Curriculum at SMKS Informatika Ciputat - Marlina, Lina; Rustandi, Roni (Universitas Pamulang, 2026)
This study aims to comprehensively describe teachers' efforts in integrating deep learning-based instruction into the Merdeka Curriculum at SMK Informatika Ciputat. The deep learning approach in education emphasizes deep conceptual understanding, critical thinking, reflection, and the ability to apply knowledge in real-world contexts. In the context of vocational education, the integration of this approach is essential to ensure that students not only master technical skills but also develop analytical, creative, and adaptive abilities in response to technological advancements. This research employs a descriptive qualitative approach to provide a comprehensive depiction of the phenomenon, particularly regarding teachers' strategies in implementing deep learning in the classroom. Data were collected through in-depth interviews, participatory observation, and documentation studies involving productive subject teachers, the school principal, and students from the Software Engineering (RPL) program. Data analysis was conducted interactively using the Miles, Huberman, and Saldana model, which includes data reduction, data display, and conclusion drawing. The findings are expected to reveal teachers’ understanding of the deep learning concept, the instructional strategies applied, and the supporting as well as inhibiting factors in its implementation. This study is expected to contribute theoretically to the development of reflective and contextual 21st-century learning models and to provide practical benefits for schools in designing policies and teacher training programs to strengthen meaningful learning in the digital era.